HUBUNGAN PRAKTEK KERJA INDUSTRI DENGAN HASIL BELAJAR SISWA DI SMK NEGERI 1 BINTAN - 27-33 . Fani Kaprila Prima (CIVED, 2013)
This research is purposed to reveal the connection between industrial practice of with productive study results for student of SMKN Bintan, which background is reality of declining student’s study result after following industrial practice, in fourth semester. This descriptive correlation research, with 64 students who is follows industrial practice in third semester as population. Based on Harry King nomogram is obtained 51 samples. Instrument that is used is questionnaire about industrial practice. Result of this research by using Product Moment Pearson found no connection between industrial practice with study result in fourth semester at SMKN 1 industrial practice. This is related to incapability of student to connect the knowledge from industrial practice with theory from school. Then, industrial practice is only providing work experience for student, not to increasing their study results. Key words :        prakerin, hasil belajar, mata pelajaran produktif